Penggunaan Media Bahan Alam Berbasis Saintifik pada Kreativitas Anak Usia Dini di Ra Yaa Bunayya - Citrasari, Sarah; Wahyuni, Annisa; Siregar, Syamsiah Depalina (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the use of scientific-based natural material media in increasing early childhood creativity in RA Yaa Bunayya. This study uses a descriptive method with a qualitative approach, involving teachers and students as respondents. Data was collected through observation, interviews, and documentation, and then analyzed by observing the development of children's creativity during the use of natural materials. The results of the study show that scientifically-based natural material media, especially in collage activities, is able to increase children's creativity. Children demonstrate the ability to explore the shapes, colors, and textures of natural materials, which encourages creative thinking and produces unique works of art. The scientific approach, which includes the stages of observing, questioning, gathering information, associating, and communicating, contributes to the improvement of critical and creative thinking skills. The resulting work shows an improvement in children's ability to experiment, imagine, and develop evaluation and collaboration skills. In conclusion, the use of scientific-based natural material media has proven to be effective in developing early childhood creativity and providing an exploratory and interactive learning experience, and supporting the development of children's imagination and critical thinking skills